Novel Intronic Mutations Introduce Pseudoexons in DMD That Cause Muscular Dystrophy in Patients - Lu, Xinguo; Han, Chunxi; Mai, Jiahui; Jiang, Xianping; Liao, Jianxiang; Hou, Yanqi; Cui, Di (Frontiers in Genetics, 2021)
Background: Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are two subtypes of muscular dystrophy diseases caused by pathogenic mutations in the DMD gene. Until now, more than 4,600 disease-causing mutations in DMD have been reported. However, only 33 mutations were deep intronic, cases with this type of mutations were limited. Methods: In this study, we used a combination of complementary DNA (cDNA) and target DNA sequencing analysis in addition to conventional whole-exome sequencing (WES). Results: Three novel hemizygous mutations IVS11 + 17811C > G (c.1331 + 17811C > G), IVS21 + 3252A > G (c.2803 + 3252A > G) and IVS40 + 362A > G (c.5739 + 362A > G) were identified in DMD patients, while a reported hemizygous mutation IVS62-285A > G (c.9225-285A > G) was found in the BMD patient. These DMD mutations lead to pseudoexon insertions, causing the generation of truncated and dysfunctional dystrophin. Conclusion: This study defines three novel and one reported intronic mutations, which can result in DMD/BMD. We also emphasize the need to combine WES and cDNA-based methods to detect the variant in the very large DMD gene in which the mutational spectrum is complex.